The integrative nature of the synoptic weather map in relation to adolescent cognitive structures and the teaching of senior secondary meteorology-climatology - Van Jaarsveld, Pieter Paul (Rhodes University, Faculty of Education, Department of Education, 1988)
A poorly consolidated concept base creates considerable difficulty amongst adolescents when it comes to the higher order task of analyzing complex, abstract and scientific weather phenomena as they appear on synoptic charts. The nature of the difficulties which they experience tends to encourage them to resort to the rote memorisation of concepts rather than understanding them. Kuhn (1962) avers that concepts, not enquiry methods, are at the core of rational thought. A well taught concept becomes a well developed mental construct which encourages understanding. It is the author's firm belief that in order for pupils to come to a thorough understanding of senior secondary meteorology - climatology and the synoptic chart, teaching of basic concepts should be graded and sequential. This thesis attempts to show the difficulties inherent in synoptic climatology. It relates these difficulties to adolescent cognitive development. Within this framework, the syllabus and past examinations of the Cape Education Department, and textbooks are examined. Teachers' views and pupils' understanding are gauged through the analyses of questionnaires and worksheets respectively. Conclusions are drawn and the problems which teachers and pupils encounter are addressed.
Keywords: Meteorology -- Study and teaching (Secondary); Climatology -- Study and teaching (Secondary); Cognition in children